2001
DOI: 10.1002/mus.1168
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric lesions of the brachial plexus

Abstract: The few studies on prognosis of obstetric lesions of the brachial plexus that are not hampered by selection bias or a short follow-up suggest that functional impairment persists in 20-25% of cases, more than commonly thought. Electromyography (EMG), potentially useful for prognosis, is often considered of little value. Denervation in the first week of life has been interpreted as evidence of an antenatal lesion, but is the logical result of the short axonal length affected. EMG performed at close to the time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
99
0
26

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 93 publications
4
99
0
26
Order By: Relevance
“…The incidence of OBPP is between 0.5% and 5 ‰ in countries with well developed obstetric services (6)(7)(8)(9)(10)(11)(12). Reduction in incidence from 1.56 per 1000 live births in 1938 to 0.28 per 1000 in 1962 was reported in New York.…”
Section: Incidencementioning
confidence: 99%
“…The incidence of OBPP is between 0.5% and 5 ‰ in countries with well developed obstetric services (6)(7)(8)(9)(10)(11)(12). Reduction in incidence from 1.56 per 1000 live births in 1938 to 0.28 per 1000 in 1962 was reported in New York.…”
Section: Incidencementioning
confidence: 99%
“…3,4 Functional recovery following OBPL is dependent not only on the number of outgrowing motor axons that reinnervate muscle fibres but also on the extent of misrouting. [5][6][7] There are indications that misrouting occurs more often in children than in adults. 5 Misrouting occurs when a regenerating axonal sprout grows into a distal basal lamina tube that is not the original one.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] There are indications that misrouting occurs more often in children than in adults. 5 Misrouting occurs when a regenerating axonal sprout grows into a distal basal lamina tube that is not the original one. 8 In misrouting, an outgrowing axon reinnervates muscle fibres in areas other than where they are intended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Various explanations have been given for this, including different innervation patterns of the infants' musculature. 13,14 Computed tomography (CT) myelography, which involves general anesthesia, a lumbar puncture, and radiation, has been shown to have high specificity for nerve root avulsion when pseudomeningoceles are seen. 15 A recent evaluation of magnetic resonance myelography found that it had a similar specificity for avulsed nerve roots as for CT myelography.…”
mentioning
confidence: 99%